2021
DOI: 10.1038/s41598-021-96416-2
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of phosphorus as soluble phosphates from aqueous solutions using chitosan hydrogel sorbents

Abstract: This manuscript presents new method of phosphorus recovery from aqueous solutions in a convenient form of readily-soluble phosphates using chitosan hydrogels. Non-modified chitosan hydrogel granules (CHs) and chitosan hydrogel granules crosslinked with epichlorohydrin (CHs-ECH) served as orthophosphate ion carriers. The developed method was based on cyclic sorption/desorption of orthophosphates, with desorption performed in each cycle to the same solution (the concentrate). The concentrations of orthophosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…In some specific cases, the contaminant might be recovered and reused for other industrial or agricultural applications. For example, Jóźwiak et al reported the recovery of P in a basic eluent (NaOH, pH 12–13), that was evaporated to obtain a sediment rich in water-soluble phosphate salts. This sediment has the potential to be used in agricultural industry .…”
Section: Desorption Methods/regeneration Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In some specific cases, the contaminant might be recovered and reused for other industrial or agricultural applications. For example, Jóźwiak et al reported the recovery of P in a basic eluent (NaOH, pH 12–13), that was evaporated to obtain a sediment rich in water-soluble phosphate salts. This sediment has the potential to be used in agricultural industry .…”
Section: Desorption Methods/regeneration Strategiesmentioning
confidence: 99%
“…For example, Jóźwiak et al reported the recovery of P in a basic eluent (NaOH, pH 12–13), that was evaporated to obtain a sediment rich in water-soluble phosphate salts. This sediment has the potential to be used in agricultural industry . However, not all contaminants can be easily recovered from the eluents, so other strategies are needed for better management and disposal.…”
Section: Desorption Methods/regeneration Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study [14], the efficiency of phosphate removal was compared using noncrosslinked chitosan hydrogel granules (CSHs) and those crosslinked with epichlorohydrin (CSHs-ECH). Two parameters turned out to be crucial for the efficiency of adsorption: the pH of the sorbate and the contact time of the sorbent with the sorbate.…”
Section: Chitosan Hydrogels In the Final Form Of Wet Or Dry Beadsmentioning
confidence: 99%
“…Meanwhile, at pH values below the pK a of chitosan, the NH 2 group is protonated into NH 3 + , which can remove anions such as phosphate [ 12 , 13 ] and arsenic [ 14 ] by forming electrostatic interactions. Moreover, phosphate (pK a1 = 2.1, pK a2 =7.2, and pK a3 = 12.3) existed as four different species (H 3 PO 4 , H 2 PO 4 − , HPO 4 2− , and PO 4 3− ) depending on the pH [ 15 ].…”
Section: Introductionmentioning
confidence: 99%